Anisotropy and shaping effects on the stability boundaries of infernal ideal MHD modes in tokamak hybrid plasmas. (25th September 2020) - Brunetti, D; Ham, C J; Graves, J P; Wahlberg, C; Cooper, W A
Abstract: Anisotropy and some limiting toroidal flow effects on the stability of nearly resonant ideal magnetohydrodynamic modes in hybrid shaped tokamak plasmas are investigated within the ideal MHD infernal mode framework. Such effects are found to alter the plasma magnetic well/hill, which can be interpreted as imparing the average curvature, and the strength of mode coupling. In line with previous results, it is found that better stability properties are achieved through deepening the magnetic well by special cases of uniform toroidal flow and parallel plasma anisotropy. Plasma shaping provides additional modifications to the magnetic well depth, whose global stabilising or destabilising effect depends on the mutual interplay of elongation, triangularity and toroidicity. Further stabilisation is achieved by weakening the mode drive in vertically elongated plasmas.